The Relationship Between Parenting Styles and Young Adolescents’ Emotional Regulation in Peninsular Malaysia - Muhammad Fiqry Mohd Yazid; Aminuddin Ibrahim Lastar (Southeast Asia Psychology Journal, 2022)
Parents’ approach should be linear and compassionate, even though the challenge may change and pattern of thoughts undergo evolution throughout the development of child. The emotional regulation among today’s young adolescents is contingent on parenting styles practiced by parents. Diana Baumrind’s Parenting Styles Model (1966) were used to support the usage of Parental Authority Questionnaire (PAQ) by Buri (1991), and Gross and John’s Emotional Regulation (2003) on describing two components of emotional regulation, which were cognitive reappraisal and expression suppression. A correlational quantitative design was used, where a total of 150 respondents, aged from 15 to 18 years old, living in Peninsular Malaysia, participated in the research, using snowball sampling method. Google Form was used to spread the survey and IBM SPSS Version 27 was used to analyze data obtained. The research found that authoritarian parenting style had greater effect to young adolescent’ emotional regulation. Result indicated that there was a correlation between authoritarian parenting style and young adolescent’s emotional regulation. The research proved that each parenting style affects emotional regulation and development in children, as it helps them prepare for situations when emotions arise, positive or bad. For future research, gender identity and age should be included to find and explore deeper, the relationship between parenting styles and emotional regulation.